Structure and Inhibition of Microbiome β-Glucuronidases Essential to the Alleviation of Cancer Drug Toxicity. Issue 9 (17th September 2015) - Wallace, Bret D.; Roberts, Adam B.; Pollet, Rebecca M.; Ingle, James D.; Biernat, Kristen A.; Pellock, Samuel J.; Venkatesh, Madhu Kumar; Guthrie, Leah; O'Neal, Sara K.; Robinson, Sara J.; Dollinger, Makani; Figueroa, Esteban; et al.
Summary: The selective inhibition of bacterial β-glucuronidases was recently shown to alleviate drug-induced gastrointestinal toxicity in mice, including the damage caused by the widely used anticancer drug irinotecan. Here, we report crystal structures of representative β-glucuronidases from the Firmicutes Streptococcus agalactiae and Clostridium perfringens and the Proteobacterium Escherichia coli, and the characterization of a β-glucuronidase from the Bacteroidetes Bacteroides fragilis . While largely similar in structure, these enzymes exhibit marked differences in catalytic properties and propensities for inhibition, indicating that the microbiome maintains functional diversity in orthologous enzymes. Small changes in the structure of designed inhibitors can induce significant conformational changes in the β-glucuronidase active site. Finally, we establish that β-glucuronidase inhibition does not alter the serum pharmacokinetics of irinotecan or its metabolites in mice. Together, the data presented advance our in vitro and in vivo understanding of the microbial β-glucuronidases, a promising new set of targets for controlling drug-induced gastrointestinal toxicity. Graphical Abstract: Highlights: Microbiome drug targets are examined from Firmicutes and Bacteroides Marked differences seen in catalytic activities and propensities for inhibition Inhibition does not alter serum pharmacokinetics of irinotecan or its metabolites Phylogeny defines major enzyme groups guided by structural features Abstract : Wallace et al. elucidate the structure and function of enzymes from the major gastrointestinal microbiome phyla that when selectively targeted by potent inhibitors can uniquely control the side effects of a cancer chemotherapeutic.